One Belt One Road Initiative: Benefits the Malay Archipelago Logistic and Culture - Mohd Saipuddin Suliman, Nordiana Ab. Jabar; Lim Ying Xuan (International Journal of Sustainable Construction Engineering and Technology, 2022)
This article aims to identify the importance of linguistic culture and logistic aspects and its relevance to One Belt One Road (OBOR) initiative in the Malay Archipelago. The objective of the writing focuses on three aspects, which are, linguistics and logistics as business generator, linguistics and logistics as a diplomatic channel and ultimately linguistics and logistics as a medium of humanitarian mission during natural disaster. This study applies qualitative approaches through close reading techniques based on previous findings in several journals that examined logistic and linguistic aspects. The scope of the research is based on the impact of OBOR inspired by The Great Wall of China to the countries in the Malay Archipelago especially Malaysia, Indonesia and its surroundings. The findings suggest that OBOR initiative will open countless business and employment opportunities, strengthen regional diplomatic ties and play a role in facilitating humanitarian missions. However, these elements will not be effective if linguistics and logistics are not systematically and consistently applied. It is hoped that this writing would be a reference for language researchers, logistics experts and business people, especially those who are looking at the prospects of OBOR initiatives in the Malay Archipelago.